Analisis Peluang Wirausaha Mahasiswa di Tengah Perkembangan Ekonomi Era Digital - Ciek Julyati Hisyam; Annisa Intan Maharani; Istiharoh Istiharoh; Pramasheila Arinda Putri (Journal of Creative Student Research, 2024)
This study aims to analyze entrepreneurial opportunities owned by university students amid economic development in the digital era. This research uses a qualitative approach with a case study method. The data collection techniques used include literature study and in-depth interviews. Data analysis was carried out using interactive data analysis, namely through the process of data reduction, data presentation, and conclusion drawing. The results showed that in opening entrepreneurial opportunities, students take advantage of technology in the digital era to find ideas, make products, and promote their entrepreneurs so that they can be reached by many consumers. The development of this digital economy affects student entrepreneurship opportunities, where increasingly sophisticated technology is one of the main supporting factors, although fierce competition is a significant challenge. These entrepreneurial opportunities can also be analyzed using Pierre Bourdieu's capital theory and arena concept.